Integrated Email Management System Based Google Application Programming Interface Using OAuth 2.0 Authorization Protocol - Zuhar Musliyana; Andita Ghaitsa Satira; Mahendar Dwipayana; Ayu Helinda (Elkawnie: Journal of Islamic Science and Technology, 2020)
Abstract : Google Apps is a service provided by Google that allows users to use Google products with their own domain names. Among the products offered by Google Apps are email (Gmail), Docs (Google Drive), and Classroom services. In addition, Google Apps also provides Application Programming Interface (API) services that can be used by developers to take advantage of various features provided by Google. Universitas Ubudiyah Indonesia (UUI) is one of the universities that use Google Apps service for managing student emails. At present, UUI student email management through Google Apps is still not integrated with academic information system data. As a result, UUI must allocate special resources for managing student emails manually. Based on these problems, this study proposes an integration system for UUI student email management using the Google Apps API. This system is designed using PHP programming. The Google Apps API authentication method uses OAuth 2.0. The results of this study indicate that student email management on Google Apps can be done through campus academic information systems. With this system, students can activate email independently without having to be registered manually to the Google Apps page by the campus email managers.Abstrak : Google Apps adalah sebuah layanan yang disediakan oleh Google yang memungkinkan pengguna dapat menggunakan produk google dengan nama domain sendiri. Di antaranya produk yang disediakan Google Apps yaitu layanan email (Gmail), dokumen (Google Drive), dan Classroom. Selain itu, Google Apps juga menyediakan layanan Application Programming Interface (API) yang dapat dimanfaatkan oleh pengembang untuk memanfaatkan berbagai layanan yang disediakan oleh Google. Universitas Ubudiyah Indonesia (UUI) merupakan salah satu universitas yang menggunakan layanan Google Apps untuk pengelolaan email mahasiswa. Saat ini pengelolaan email mahasiswa UUI melalui Google Apps masih belum terintegrasi dengan data sistem informasi akademik. Akibatnya UUI harus mengalokasikan sumber daya khusus untuk mengelola email mahasiswa secara manual. Berdasarkan permasalahan tersebut penelitian ini mengusulkan sistem integrasi pengelolaan email mahasiswa UUI menggunakan API Google Apps. Sistem ini dirancang menggunakan pemograman PHP. Metode autentikasi API Google Apps menggunakan OAuth 2.0. Hasil penelitian ini menunjukkan pengelolaan email mahasiswa pada Google Apps dapat dilakukan melalui sistem informasi akademik kampus. Dengan adanya sistem ini mahasiswa dapat melakukan aktivasi email secara mandiri tanpa harus didaftarkan secara manual ke halaman Google Apps oleh pengelola email kampus.